A Comprehensive Review on the Therapeutic Versatility of Imidazo [2,1-b]thiazoles - Shareef, Mohd A.; Khan, Irfan; Babu, Bathini Nagendra; Kamal, Ahmed (Current Medicinal Chemistry, 2020)
Background: Imidazo[2,1-b]thiazole, a well-known fused five-membered hetrocycle is one of the most promising and versatile moieties in the area of medicinal chemistry. Derivatives of imidazo[2,1-b]thiazole have been investigated for the development of new derivatives that exhibit diverse pharmacological activities. This fused heterocycle is also a part of a number of therapeutic agents. Objective: To review the extensive pharmacological activities of imidazo[2,1-b]thiazole derivatives and the new molecules developed between 2000-2018 and their usefulness. Method: Thorough literature review of all relevant papers and patents was conducted. Conclusion: The present review, covering a number of aspects, is expected to provide useful insights in the design of imidazo[2,1-b]thiazole-based compounds and would inspire the medicinal chemists for a comprehensive and target-oriented information to achieve a major breakthrough in the development of clinically viable candidates.
Keywords: antimicrobial